Impact of mining on the metal content of dust in indigenous villages of northern Chile - Zanetta Colombo, Nicolás; Fleming, Zoë L.; Gayo, Eugenia M.; Manzano, Carlos A.; Panagi, Marios; Valdés, Jorge; Siegmund, Alexander (Environment international, 2022)
Indigenous communities from northern Chile have historically been exposed to the impacts of massive copper industrial activities conducted in the region. Some of the communities belonging to the Alto El Loa Indigenous Development Area are located less than 10km from the “Talabre'' tailings dam, which contains residues from copper production and other metals that can be toxic to human health (e.g., As, Sb, Cd, Mo, Pb). Given the increasing demand of copper production to achieve net-zero emission scenarios and concomitant expansions of the tailings, the exposure to toxic metals is a latent risk to local communities. Despite the impact that copper production could generate on ancestral communities from northern Chile, studies and monitoring are limited and the results are often not made accessible for local communities. Here, we evaluate such risks by characterizing metal concentrations in dust collected from roofs and windows of houses from the Alto El Loa area.
Gesehen am 13.12.2022